Perkawinan yang Tidak Dicatatkan dalam Masyarakat Hindu di Bali - Pande Putu Gita Yani; I Ketut Sukadana; Luh Putu Suryani (Warmadewa Press, 2021)
According to Article 2 of Law Number 1 of 1974 concerning Marriage, that marriage is considered valid if carried out according to religion and belief, and registered with civil registration. The divorce process is not stated in the Hindu community in Bali and due to marriage which is not recorded in the Hindu community in Bali. The research method uses a type of normative research, legal research that examines written law and divided aspects. Over time, problems often arise as a result of disharmony in domestic life. As a divorce arises, divorce is the end of a marriage. In Law No. 1 of 1974 the termination of marital ties can be caused by death, divorce, and court decisions. In the trial the divorce case does not have a marriage certificate so it can be replaced with a statement from the village.